Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat pada Pasien Hipertensi di Puskesmas Tutukembong, Tanimbar - Jekris Ens Luturmas; Iman Haryana; Josepina Mainase; Elpira Asmin; Irwan Irwan (Sehat Rakyat: Jurnal Kesehatan Masyarakat, 2025)
Hypertension is one of the most common diseases among adults and a leading cause of morbidity. This condition makes hypertension a significant health challenge in various countries, including Indonesia. Medication adherence is crucial for hypertensive patients in controlling their blood pressure. Research suggests that medication adherence can be influenced by a person's knowledge. This study aims to determine the relationship between the level of knowledge of hypertension patients and compliance in taking medication in hypertension patients at the Tutukembong Community Health Center, Tanimbar Islands Regency. This research is an analytical observational study using quantitative methods with a cross-sectional approach. The sample in this study consisted of 97 individuals (hypertension patients), selected using a purposive sampling technique. Test Chi-Square generate valuep0.036, while the contingency coefficient showed a figure of 0.253. These findings indicate a significant relationship with low strength between the level of knowledge and compliance in taking medication in hypertension patients at the Tutukembong Community Health Center, Tanimbar Islands Regency. There is a significant but weak relationship between the level of knowledge of hypertension patients and compliance with taking medication in hypertension patients at the Tutukembong Community Health Center, Tanimbar Islands Regency. These results indicate that increasing knowledge alone is not enough; other approaches such as motivation, family support, regular monitoring, and other factors are needed to improve compliance in hypertensive patients.